Evidence for the presence of the Portuguese oyster, Crassostrea angulata, in northern China - Lapegue, Sylvie; Batista, Frederico; Heurtebise, Serge; Yu, Ziniu; Boudry, Pierre (The National Shellfisheries Association, 2004)
The Pacific oyster, Crassostrea gigas (Thunberg), and the Portuguese oyster, C. angulata (Lamarck), are two closely related taxa. Although these two taxa were both introduced from Asia into Europe. one (C. gigas) was voluntarily introduced in the early 1970s, whereas the other (C. angulata) was presumed to be present in Europe for at least four centuries, but nearly disappeared because of disease. Few C. angulata populations remained in southern Portugal, Spain and Morocco and their putative origin was traced in Taiwan. The present paper reports evidence for its presence in Northern China. We reanalyzed recently published mitochondrial cytochrome oxidase C subunit I (COI) sequence data from presumed Dalianwan oysters (C. talienwhanensis) and compared them with those of C. gigas and C. angulata. Additionally, two new C. angulata haplotypes from Portugal were identified. The results clearly showed that some of the C. talienwhanensis sequences cluster with C. angulata sequences. The relative divergence between C. gigas, C. angulata, and C. talienwhanensis haplotypes indicated that C. angulata-like oysters are present in northern China. This opens new perspectives in terms of genetic resources and population genetics of C. gigas and C. angulata, two oyster species of aquacultural importance.